WEBLOG: ALTERNATIF MEDIA PROMOSI BAGI SENIMAN - Joko Subiharto (Ars: Jurnal Seni Rupa dan Desain, 2007)
As an artist, the key to promoting more artwork is maximizing its exposure. The internet is anincreasingly popular tool for promoting original art, unci if done properly, can be quite profitable. One o f themost effective (and free!) online marketing tools for artists is the blog. Artist blogs provide an easy way todisplay your art, discuss your creative process, post exhibition announcements and more. Best o f all, blogsrequire no working knowledge o f HTML and the search engines love their dynamic content.1Key words: weblog, promotion, artist